Influence of various dominant trees on phytosociology of under storey herbaceous vegetation - Sharma, Beena; Sharma, Kavita (Recent Research in Science and Technology, 2013)
The Western foot hill gaps of Central Aravallis are stabilized with indigenous and exotic tree species. In the present investigation three different sites were selected, i.e. Pushkar Valley sand dunes (dominated by Acacia tortilis), Leela Sewri sand dunes (dominated by A.senegal) and Pachkund sandy plains (dominated by Eucalyptus camaldulensis). Herbaceous flora under the various tree plantations was listed separately to determine the influence of the tree species on phytosociological parameters of herbaceous vegetation. Studies on the influence of individual tree species on the structure of herbaceous vegetation show that species responses vary under different plantations. It is clear from the data that many species which show high value of frequency may not be dominants with respect to IVI (Importance Value Index). Grasses are common for all the sites of study. However, some species respond differentially and to some extent dominance of a species under a particular tree plantation may affect the soil properties and floor dynamics.